Synchronous bilateral lung adenocarcinomas associated with vulvar rhabdomyosarcoma in a 15-year-old girl - Tatsuo Furuya; Hiroaki Tsunezuka; Satoru Okada; Daishiro Kato; Junichi Shimada; Mitsuru Miyachi; Tomoko Iehara; Hajime Hosoi; Masayoshi Inoue (Elsevier, 2018)
Pediatric malignancies are thought to be risk factors of second malignant neoplasms. However, lung cancer associated with rhabdomyosarcoma is extremely rare. When multiple pulmonary lesions are observed in cancer patients, resection is necessary to distinguish them from metastatic lesions. We report an extremely rare case of synchronous bilateral multiple lung cancers showing ground glass nodules (GGNs) associated with rhabdomyosarcoma in a 15-year-old girl with vulvar rhabdomyosarcoma. When we identify GGNs in adolescents with a history of rhabdomyosarcoma, we should consider lung cancer as a differential diagnosis in addition to pulmonary metastasis usually showing solid nodule. In the present case with tiny lesions, surgical resection using lipiodol-marking helped to ensure both an early diagnosis and curative treatment. Keywords: Synchronous bilateral multiple lung cancers, Adolescent, Rhabdomyosarcoma